Dietary supplementation with Andrographis paniculata and Orthosiphon stamineus improved growth performance of broiler chicken - Malahubban, Masnindah; Alimon, Abdul Razak; Sazili, Awis Qurni (2011)
This study was conducted to determine the effect of different levels of Andrographis paniculata and Orthosiphon stamineus on growth performance of broiler chicken. Two hundred eighty (N=280) of Cobb broiler chickens from 3 to 6 weeks of age were tested. The chickens were fed on basal diet (Control), basal diet with 0.2% A. paniculata (0.2%AP), basal diet with 0.4% A. paniculata (0.4%AP), basal diet with 0.8% A. paniculata (0.8&PA), basal diet with 0.2% O. stamineus (0.2%OS), basal diet with 0.4% O. stamineus (0.4%OS), basal diet with 0.8% O. stamineus (0.8%OS). The result revealed that the mean bodyweight and weight gain of all treatment groups were significantly (P<0.05) higher as compared to the body weight of control group. We concluded that chicken fed on diet supplemented with certain level of medicinal plants, A. paniculata and O. stamineus could increased bodyweight gain even at insignificant volume of feed intake within treatments with diet supplemented with 0.8% O. stamineus was the highest increase in body weight.